Hubungan Kesepian dengan Insomnia pada Lansia di Rumah Pelayanan Sosial Semarang - Fika Riyan Syah; Moch Aspihan; Iskim Lutfha (Journal of Health, Medical, and Psychological Studies, 2026)
Background: Loneliness is one of the major psychosocial problems commonly experienced by elderly individuals, particularly those living in social care institutions. Prolonged loneliness may cause negative effects on mental and physical health, including sleep disturbances such as insomnia. Objective: This study aimed to determine the relationship between loneliness and insomnia among elderly people at the Social Service Home in Semarang. Methods: This study employed a quantitative design with a cross-sectional approach involving 135 elderly respondents selected using consecutive sampling. Data were collected using the UCLA Loneliness Scale and the KSPBJ-IRS questionnaire. Data analysis was performed using the Somers’ d test. Results: The results showed that most respondents experienced moderate levels of loneliness (51.9%) and high levels of insomnia (51.9%). The Somers’ d test indicated a p-value of 0.000 (p < 0.05) with a correlation coefficient (r) of 0.794, indicating a strong and significant relationship between loneliness and insomnia. Conclusion: There is a strong and significant relationship between loneliness and insomnia among elderly individuals. Higher levels of loneliness are associated with higher levels of insomnia.